The Performance of Election Organizers in the Implementation of the 2020 Regional Elections During The COVID-19 Pandemic - Dimas Subekti; Suswanta Suswanta; Muchamad Zaenuri (Universitas Sultan Ageng Tirtayasa, 2021)
This study explains the performance of election organizers in implementing the 2020 regional election during the COVID-19 pandemic. This type of research is descriptive qualitative. This study's data comes from important scientific journal papers and reliable Indonesian mainstream media news sources like tempo.com, kompas.com, lokadata.id, Republika.co.id, tribunnews.com, and CNN Indonesia. The study's findings suggest that election organizers have no plans to postpone the simultaneous regional head elections scheduled for December 9, 2020, for the simple reason of ensuring the people's constitutional right to be elected and vote. It is impossible to predict when the COVID-19 pandemic will stop. The government does not want task executors to lead the areas. During the simultaneous regional elections on December 9, 2020, misinformation and coordination errors occurred between the government and the Election Supervisory Body, and the task force for the acceleration of handling COVID-19.